2017
DOI: 10.1016/j.semcancer.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial determinants of cancer health disparities

Abstract: Mitochondria are involved in the generation of energy, cell growth and differentiation, cellular signaling, cell cycle control, and cell death. To date, the mitochondrial basis of cancer disparities is unknown. The goal of this review is to provide an understanding and a framework of mitochondrial determinants that may contribute to cancer disparities in racially different populations. Mitochondria, which are multi-functional, have been implicated in the initiation and progression of cancers in relation to met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 409 publications
0
50
0
2
Order By: Relevance
“…Beyond cognitive aging, because of humanin’s role in other diseases including cardiovascular disease and diabetes, circulating levels of humanin could also contribute to additional diseases that disproportionately affect African Americans. The mitochondria have been implicated in health disparities because of their central importance in many diseases and the uniparental inheritance of the genome 46 . The role of humanin in health disparities is a novel concept that further implicates the mitochondria in the biological basis of health disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond cognitive aging, because of humanin’s role in other diseases including cardiovascular disease and diabetes, circulating levels of humanin could also contribute to additional diseases that disproportionately affect African Americans. The mitochondria have been implicated in health disparities because of their central importance in many diseases and the uniparental inheritance of the genome 46 . The role of humanin in health disparities is a novel concept that further implicates the mitochondria in the biological basis of health disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Koochekpour et al (7) observed mitochondrial DNA depletion in prostate tissue from African American patients and suggested that lower mitochondrial DNA content contributes to differences by race in prostate cancer incidence and progression. Additional research has focused on both germline and somatic mutations in mitochondrial DNA in prostate cancer and other malignancies with variable findings (8). Finally, use of metformin as a prostate cancer chemopreventive has shown some promise, as it has been linked to reduced risk of recurrence, metastatic disease, and death in men with concomitant type 2 diabetes (9).…”
Section: Oxphos and Mitochondrial Dysfunction Linked To Disparitymentioning
confidence: 99%
“…наиболее энергозатратных органов, для функционирования которых необходим постоянный пул макроэргов [19,20,21]. Настоящее исследование было сосредоточено на оценке респирометрической функции митохондрий в условиях патологий ишемического генеза, при которых наблюдается существенный энергодефицит, прямо характеризующий деятельность митохондрий -фокальной ишемии, ЧМТ, инфаркте миокарда и мышечной дисфункции [22].…”
Section: обсуждение результатовunclassified